ChemInform Abstract: Four‐Component Electrophilic Difunctionalization of Olefins Using Sulfonic Acids, Cyclic Ethers, and NBS. Issue 6 (21st January 2016) - Sohail, Muhammad; Khan, Muhammad; Zhang, Yixin; Peng, Chang; Chen, Qin; Zhao, Zongbao K.
Abstract: The novel, highly regio‐ and diastereoselective four‐component reaction affords sulfonate ester derivatives.